A unique mechanism for thiolation of serum albumins by disulphide molecules. (9th October 2019) - Nakashima, Fumie; Shibata, Takahiro; Uchida, Koji
Abstract: Protein S -thiolation is a reversible oxidative modification that serves as an oxidative regulatory mechanism for certain enzymes and binding proteins with reactive cysteine residues. It is generally believed that the thiolation occurs at free sulphydryl group of cysteine residues. Meanwhile, despite the fact that disulphide linkages, serving structural and energetic roles in proteins, are stable and inert to oxidative modification, a recent study shows that the thiolation could also occur at protein disulphide linkages when human serum albumin (HSA) was treated with disulphide molecules, such as cystine and homocystine. A chain reaction mechanism has been proposed for the thiolation at disulphide linkages, in which free cysteine (Cys34) is involved in the reaction with disulphide molecules to form free thiols (cysteine or homocysteine) that further react with protein disulphide linkages to form the thiolated cysteine residues in the protein. This review focuses on the recent finding of this unique chain reaction mechanism of protein thiolation.